Coevolutionary causes and consequences of high-fidelity mimicry by a specialist brood parasite - Lund, Jess (Department of Biological Sciences, 2022)
Mimicry is often invoked as a classic demonstration of the power of natural selection. However, mimicry systems are diverse and the accuracy of mimicry, or mimetic fidelity, varies from crude to near-perfect. There is growing evidence that low-fidelity mimicry is the norm, with cases of high-fidelity mimicry being rarer. This is particularly evident in avian interspecific brood parasites, which are birds that lay their eggs in the nests of other species, or ‘hosts'. A possible rare example of a “perfect mimic” is the African cuckoo Cuculus gularis (a specialist parasite of fork-tailed drongos Dicrurus adsimilis) which, to the human eye, exhibits some of the most sophisticated mimicry seen in a brood parasite-host system. In this work, I quantify the degree of mimetic fidelity in this system and investigate its consequences on the two antagonists, using experimental, observational and genetic data I collected in the field in Zambia. In Chapter 1 I first define perfect mimicry, and explore how mimetic fidelity can be quantified. I then review the factors responsible for the variability in mimetic fidelity among different mimicry systems. In Chapter 2 I use quantitative measures of egg colour and pattern, from models that approximate avian vision, to show that mimicry of drongo eggs by African cuckoos is near-perfect. I subsequently use field experiments and simulations to show that a high degree of interclutch variation (egg ‘signatures') means that drongos still have the upper hand in the arms race against this near-perfect mimic. In Chapter 3 I investigate the genetic architecture of perfect mimicry by comparing cuckoo egg phenotypes to their mitochondrial DNA haplotypes, providing evidence that the African cuckoo likely shows bi-parental inheritance of egg phenotype. Together these results highlight the effectiveness of egg signatures as a defence against brood parasites, even when mimicry shows high accuracy and precision, and underline the role of mechanistic factors in enabling high-fidelity mimicry to evolve.